Efek diumumkannya kasus pertama Covid-19 terhadap harga saham dan total saham yang diperdagangkan - Siswantoro Siswantoro (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: This research aimed to find out whether there are significant differences between stock prices and stock trading totals before and after the announcement of the first case of Covid-19 in hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange. Research methodology: Data were acquired from the website www.finance.yahoo.com with a sample of 20 companies. The observation period in this study was 60 days, from 20 January to 14 April 2020. The method in this research was comparative study. Data were analyzed through the Wilcoxon Signed Rank Test. Results: The results show there are significant differences between stock prices and stock trading totals before and after the announcement of the first case of Covid-19, where the significant value of each variable is 0,000 < 0.05. Limitations: This research only observed one research object and the observation period was only 60 days. Besides, it only compared two variables. Contribution: The companies must change their sales strategy to be able to raise stock prices and stock trading totals. Keywords: Stock prices, Stock trading totals, Hotel, Restaurant, Tourism companies, Covid-19